A Newly Developed Variable Stiffness Duodenoscope for Diagnostic and Therapeutic Endoscopic Retrograde Cholangiopancreatography. (11th November 2010) - Itoi, Takao; Sofuni, Atsushi; Itokawa, Fumihide; Kurihara, Toshio; Tsuchiya, Takayoshi; Ishii, Kentaro; Tsuji, Shujiro; Ikeuchi, Nobuhito; Umeda, Junko; Moriyasu, Fuminori; Kasuya, Kazuhiko; Tsuchida, Akihiko
Abstract : The aim of this study is to evaluate a prototype variable stiffness duodenoscope (VSD) for diagnostic and therapeutic ERCP in comparison with standard duodenoscopes. We performed retrospective analysis on the success rate of intubation of the second duodenum, overall procedural success rate, and comparative frequency of the necessity to change duodenoscopes from standard JF-260V and TJF 260V or to change stiffness using the VSD. A total of 213 nonconsecutive procedures in 196 patients with pancreaticobiliary diseases. There was no statistically significant difference in endoscope intubation rate or technical success rate between the different duodenoscopes. In one patient with severe duodenal stenosis, the VSD using the moderately stiff mode allowed the major papilla to be reached when the TJF-260V endoscope could not. There were no serious procedure-related adverse events. In conclusion, while the VSD performed well, the present models do not appear to offer obvious advantages over the standard duodenoscopes for routine diagnostic and therapeutic ERCP. Prospective studies may be warranted to identify those patients who would benefit from this new technology.